Analisis Penerapan Terapi Ankle Pump Exercise Kombinasi Elevasi Kaki 30o Pada Ny.J dengan Penyakit Ginjal Kronik (Pgk) yang Menjalani Hemodialisis di Ruangan Hemodialisa Melati RSUP. Kandou Manado - Pangandaheng, Velisia; Larira, Dina Mariana; Toar, Juwita Moreen (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background. Stroke is a neurological change caused by disturbances in blood circulation to parts of the brain. Hemiparesis is a complication that may be experienced, so passive range of motion exercises are needed. The prevalence of stroke cases in Indonesia is high, with the North Sulawesi region ranking third. Objective. Analysing the results of providing passive ROM intervention for muscle strength in patients with ischaemic stroke in the Edelweis 1 hospital room. Prof. Dr R.D. Kandou, Manado. Method. This scientific work uses a case study method on the patient Mr AW, who has a diagnosis of ischaemic stroke. Results. The nursing intervention provided was energy management by providing passive ROM for 4 days of patient care, showing an increase in muscle strength in the left extremities from 4/4 to 5/5 and the right from 1/1 to 4/3. Discussion. ROM exercises are performed on patients with impaired physical mobility. Passive ROM is provided by helping to move the affected extremity. ROM exercises are given to patients twice a day for 15-20 minutes, carried out at a pre-determined and consistent time. Conclusion. Providing passive ROM (range of motion) exercises can increase muscle strength in stroke patients or those who experience decreased muscle strength. Keywords: Ischaemic stroke; Muscle strength; Passive range of motion (ROM).